Resiliência em uma cadeia de suprimentos automotiva : o papel da integração interfuncional - Poberschnigg, Tayanne Ferraz da Silva (2018)
Over the years, the companies have been facing many challenges, including the management of global supply chains. Besides that, managers have to deal with economic instability and political and environmental changes, a context that presents risks of disruptions in the supply chains. Thus, the literature of supply chain management has discussed about resilience, a concept related to the supply chain’s ability to cope with changes quickly, being able to recover from a disruption or other event that affects a supply chain. This is achieved by the presence of supply chain capabilities, which may reduce vulnerabilities, as well as by the knowledge gained from previous disruptions, facilitating a faster and more efficient response to certain events. Although the literature has discussed resilience broadly, few researches are focused on connecting this subject with the integration theory, especially regarding cross-functional integration. Thus, this study sought to analyze how cross-functional integration processes could be practiced in order to support supply chain resilience. A total of eighteen in deep interviews were conducted mostly with managers from six different organizations of the automotive industry: two suppliers, one focal industry and three customers. This sector is important to Brazilian economy and it is recovering from the Brazilian financial crisis occurred on 2015, being this a good opportunity to discuss the impacts of this event. Besides that, the organizations that contributed to this research are part of a global supply chain, which make it more vulnerable due to the extent of the chain. The analysis involved the identification of the main disruptions and capabilities in the automotive supply chain. In addition, many cross-functional integration factors were discussed in each company of the supply chain. All this information enabled to make links between resilience and integration literature. Findings show that the most frequent disruptions in the automotive supply chain are lack of product, interruption of production, delivery delay, organizational bankruptcy and sale loss. About the supply chain capabilities, in this study the least important is redundancy. Flexibility, Adaptability, Collaboration, Visibility and Agility matter, although the last two should be more developed in the supply chain according to some interviewees. Besides, the cross-functional integration factors highlighted among the companies are: cross-functional meetings, adequate communication, longevity of relationships, cross-functional training, recognition of interdependence and consideration to informal groups. Through these factors, among others, it’s possible to avoid disruptions in the supply chain, as well as help to develop organizational and supply chain capabilities.